Is there surplus labor in rural India? - Andrew D. Foster; Mark R. Rosenzweig (Yale University, Economic Growth Center, 2010)
We show empirically using panel data at the plot and farm level and based on a model incorporating supervision costs, risk, credit-market imperfections and scale-economies associated with mechanization that small-scale farming is inefficient in India. Larger farms are more profitable per acre, more mechanized, less constrained in input use after bad shocks, and employ less per-acre labor than small farms. Based on our structural estimates of the effects of farm size on labor use and the distribution of Indian landholdings, we estimate that over 20% of the Indian agricultural labor force is surplus if minimum farm scale is 20 acres.
Keywords: O13; O16; O53; 330; agriculture; India; scale; profits; labor; tractors